Pola Asuh Orang Tua Dalam Pembentukan Akhlaq Anak Di Dusun Krajan Desa Glundengan Kecamatan Wuluhan Tahun 2024/2025 - Hardiansyah, Ahmad Iko; Setiawan, Bahar Agus; Tamami, Badrut (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2025)
This study aims to analyze parenting patterns in shaping children's morals in Krajan Hamlet, Glundengan Village, Wuluhan District, in 2024/2025. The background of this study is concern about the behavior of children who show symptoms of moral decline, such as lying, contradicting parents, and not practicing Islamic attitudes in everyday life. Using a qualitative approach with a case study method, data was obtained through observation, in-depth interviews, and documentation of parents and children in the environment. The results of the study showed that the parenting patterns applied varied greatly, but the majority did not fully refer to the principles of Islamic education. Internal factors such as parents' busyness and lack of understanding in the family, as well as external factors such as environmental influences and digital media, are obstacles to the implementation of effective parenting patterns. This study emphasizes the importance of the active role of parents as primary educators and the need to strengthen moral values ​​in child care to create a generation with noble morals.